PERBANKAN SYARI’AH DI INDONESIA; Antara Peluang dan Tantangan - Muslim, Ahmad Shobiri (UNIVERSUM, 2016)
The muslim are in happiness with the development of Islamic bank. If Islamic bank in Indonesia compared with Islamic bank all part of the world, Indonesia is the biggest one, biggest in totality of Islamic bank, biggest in totality of Customer, DPS, banker and biggest in totality of university which offers Islamic bank program. However it is very ironic lot of muslim respond it negatively. The fact shows us that muslim customers are lower than non muslim customers of Islamic bank. Really Islamic bank is a bank based on shariate principles in operationalization and has different characteristics and principles it compared with conventional bank. Principles of Islamic bank are 1. Opposed to usury, 2. Sell and by priority, 3. Mutual helping and corporation, 4. Justice and, 5. Corporation increasing achievement. In legality perspective Islamic bank clearly based on low, in operational activities, those are 1. Constitution and regulation of Indonesia bank, 2. Fatwa of DSN (Dewan Syari’ah Nasional) 3. Other conventional constitutional regulation, so Islamic bank is permitted in Islamic low, otherwise Islamic bank permitted in Islamic low, Islamic bank has many opportunities and some challenges and need best solution. Those challenges are 1. Limitation in human recourses, 2. Limitation in capital, 3. Limitation in socialization and education to community, 4. Limitation in loyalty of customer, 5. Limitation of official network an ATM.Keywords; Islamic bank, opportunity, challenge.